The association of eicosanoids with lung structure and function: Findings from the Multi-Ethnic Study of Atherosclerosis lung study and Framingham Heart Study - Mythri Ambatipudi; Jenna N. McNeill; Athar Roshandelpoor; Mona Alotaibi; Louisa A. Mounsey; Eric Hoffman; George O’Connor; Seung Hoan Choi; Norrina B. Allen; R. Graham Barr; Mohit Jain; Susan Cheng; et al. (PLoS ONE, 2026)
Background Eicosanoids are bioactive signaling lipids that have roles in airway remodeling, smooth muscle hypertrophy, emphysema and pulmonary fibrosis via mediation of pro- and anti-inflammatory pathways. Specific eicosanoids have been associated with lung diseases such as asthma and pulmonary fibrosis, yet their association with lung function more broadly is not completely understood. We aimed to investigate the association of eicosanoids and related metabolites with early changes in lung function and structure. Methods We performed comprehensive profiling of over 250 eicosanoids and eicosanoid-related metabolites using directed non-targeted mass spectrometry in the Multi-Ethnic Study of Atherosclerosis (MESA) Lung Study with independent validation in the Framingham Heart Study (FHS). We performed cross-sectional analysis of the associations between metabolites and lung function as assessed by spirometry and quantitative lung measures on computed tomography (CT). Results Among 3384 participants (mean age 63 ± 10 years, 51% women), 51 metabolites were associated with lung function in MESA Lung (22 with % predicted FEV 1 , 18 with % predicted FVC, and 25 with FEV 1 /FVC ratio), with 24 validated among FHS participants. Of these 51 metabolites, 27 were associated with obstructive lung physiology, including linoleic acid derivatives (9-HODE) and other long-chain fatty acids (hydroxyhexadecanoic acid, hydroxyoctadecanoic acid) associated with higher odds. Fourteen metabolites were associated with restrictive physiology, including putative dihydroxy-20:3 and an LTB3 analog associated with lower odds, and omega-3 fatty acids (EPA, stearidonic acid) associated with higher odds. Conclusions Specific eicosanoids and eicosanoid-related metabolites including linoleic acid derivatives and long-chain fatty acids were associated with obstructive, and leukotrienes and omega-3 fatty acids with restrictive lung physiology. These findings highlight bioactive lipids involved in both pro- and anti-inflammatory pathways as potential influencers of lung function and may serve as future therapeutic targets early in lung disease development.